2021
DOI: 10.1051/bioconf/20213800007
|View full text |Cite
|
Sign up to set email alerts
|

Predictive distribution for Salvia aethiopis (Lamiaceae) in Middle Asian Region based on climatic modelling

Abstract: Geospatial investigation of distribution Salvia aethiopis L. (Lamiaceae) on the eastern limits of the range is performed using climatic modeling by MAXENT approach. Climatic conditions for the 33 local populations of the species as well as territories neighbouring to them were examined in detail, using concepts of nestle-cells and a small polygone. According to obtained results, the most suitable climatic conditions are in only two small polygons (SP) around local populations with coordinates 69.96E:42.48N and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Using SDMs for studying rare plant species in Uzbekistan is in the initial stage now. Only a few studies were carried out (Baikov et al 2021; Khujanov, 2021; Mavlanov et al 2021) and most of them were conducted using MaxEnt (Philips et al 2006), which is considered the most powerful machine learning algorithm with an uncomplicated graphical user interface, which made MaxEnt the most comfortable and popular technique for researchers in last years (Philips et al 2017). However, numerous studies demonstrated that Random Forest and other machine learning techniques in some cases are more efficient than MaxEnt (Williams et al 2009; Duan et al 2014; Mi et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Using SDMs for studying rare plant species in Uzbekistan is in the initial stage now. Only a few studies were carried out (Baikov et al 2021; Khujanov, 2021; Mavlanov et al 2021) and most of them were conducted using MaxEnt (Philips et al 2006), which is considered the most powerful machine learning algorithm with an uncomplicated graphical user interface, which made MaxEnt the most comfortable and popular technique for researchers in last years (Philips et al 2017). However, numerous studies demonstrated that Random Forest and other machine learning techniques in some cases are more efficient than MaxEnt (Williams et al 2009; Duan et al 2014; Mi et al 2017).…”
Section: Introductionmentioning
confidence: 99%